Ethical behaviors by leaders act as a stimulant to the wellbeing of employees by restraining workplace embitterment - Saleem, Ammara; Bashir, Mohsin; Abrar, Muhammad (Frontiers in Public Health, 2022)
Prior studies have revealed that leaders' ethical behaviors significantly influence employees' wellbeing. However, it's unclear how to increase the positive impact of leaders' ethical behaviors on employees' wellbeing by overseeing the negative workplace emotion. So, this study examines the salient concern of leaders' ethical behaviors that affect employees' negative emotions (workplace embitterment) and, consequently, their wellbeing according to appraisal theories of emotions. The study also investigates the active role of followers' core self-evaluation in moderating the impact of leaders' ethical behaviors on followers' emotions and wellbeing via the mediational chain. Data is collected in two-time intervals with 6 weeks interims through a structured questionnaire from 398 academics of public sector universities in Pakistan. The structured equation modeling and Process Macro 2017 are the tools for data analysis. Findings of this study show that (1) ethical behaviors by leaders have a negative impact on employee workplace embitterment, (2) workplace embitterment completely mediates the association between ethical behaviors of leaders and employee wellbeing, and (3) when leaders do not exhibit ethical behaviors, workplace embitterment is lessened showing high core self-evaluations by employees. In addition, the study findings also reveal that employees' core self-evaluation moderates the effect of leaders' ethical behaviors through workplace embitterment. This study validates the significant role of a leader's ethical behaviors in nourishing employee wellbeing by preventing negative emotions. The study is also significant as it examines how followers' attribute core self-evaluation: (1) can be a substitute for leaders' ethical behaviors and (2) can actively modify the effect of leaders' ethical behaviors on followers' negative emotions and then wellbeing. The study also discussed its contributions in theory and to organizations.